Upgrading the Students’ English Descriptive Essay Writing Competence through Mind Mapping Technique - Khadijah Maming; Khairunnisa Hatta; Sianna Sianna; Husnul Muarifah (Musamus Journal of Language and Literature, 2022)
Based on the results of observations at SMP Negeri 1 Pinrang, South Sulawesi, Indonesia, the researcher found that teaching technique were needed in an attractive teaching and learning system, so that the learning process could attract students interest, especially in English subject. The application of mind mapping technique is an effective way to upgrade their writing particularly in constructing descriptive essay, it helps students to think and express their ideas. The purpose of this research is to find out whether the application of mind mapping technique can upgrade the achievement of students writing ability in class VII at SMP Negeri 1 Pinrang, South Sulawesi, Indonesia. This research employed quasi-experiment method by using two classes with form pretest and posttest to measure their writing ability. The research sample was chosen by randomly and the sample from this research was class VII3 as the experimental class with total 31 students and class VII11 as the control class with total 31 students. The data analysis result showed that the students writing achievement get improvement. This statement is proved from their mean score of students’ post-test in the experimental class (73,84) is higher than their mean score in the pre-test (60,48). It is concluded that the application of mind mapping technique upgrades the students’ competence in writing descriptive essay.